تجريب المناهج الدراسية في العملية التعليمية - د. محمد الأمين محمد يوسف كبر (White Nile Journal for Studies and Research, 2015)
Abstract process educational the in curricula Experimentationof curricula of experimentation the of objectives the determine to aimed study The researcher The life of aspects all in changes speedy and rapid the of light in and curriculum for center national the at researchers and experts selected a as considered themselves and population research a as research educational teaching preparing with entrusted are they as (experts 45) sample purposive statistical for test square chi and conducted was questionnaire A curriculum the of one results following the to arrived research The used was significance the of quality the determine to is experimentation of objectives important most and professional the have teachers that ascertain suitability its and curriculum educational achieve curriculum, intended the teach to capabilities academic pupils of age the for suitable are subjects various the that ensure and, objectives of importance The circumstances changing of light in needs their and participating the of confidence the in appears curriculum of experimentation. public to leads quality high its and curriculum the of suitability the in partners It aspects positive the strengthens and difficulties overcome helps satisfaction in environments different the with compatible is curriculum the that ensures also applied is it which notes teachers the are experimentation of forms and types important most The educational and curriculum for center national the at experts by visits field Interviews, professionals educational and teachers meet to states the to research. is curriculum the where, teachers -school with level field the in communication.. with communicate to technology communication modern of use the and taught opinions pupils the know to need the recommended study The society whole the curriculum the about judgments to rushing against cautioned, curriculum the of curriculum entire the cover that research experimented more out carry to and field